2020
DOI: 10.1016/j.scitotenv.2020.138884
|View full text |Cite
|
Sign up to set email alerts
|

GIS-based spatial modeling of COVID-19 incidence rate in the continental United States

Abstract: Journal Pre-proof J o u r n a l P r e -p r o o f 2 GIS-based Spatial Modeling of COVID-19 Incidence Rate in the Continental United States AbstractDuring the first 90 days of the COVID-19 outbreak in the United States, over 675,000 confirmed cases of the disease have been announced, posing unprecedented socioeconomic burden to the country. Due to inadequate research on geographic modeling of COVID-19, we investigated county-level variations of disease incidence across the continental United States. We compiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
608
2
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 610 publications
(651 citation statements)
references
References 32 publications
24
608
2
17
Order By: Relevance
“…Wu et al and Mollalo et al, in nationwide studies in the USA, showed that exposure to PM increased COVID-19 mortality and severity 42,50,51 . Setti et al reported a significant relationship between PM and experiencing COVID-19 in Italy (January 1, 2020) 52 .…”
Section: Demographic and Social Factorsmentioning
confidence: 98%
“…Wu et al and Mollalo et al, in nationwide studies in the USA, showed that exposure to PM increased COVID-19 mortality and severity 42,50,51 . Setti et al reported a significant relationship between PM and experiencing COVID-19 in Italy (January 1, 2020) 52 .…”
Section: Demographic and Social Factorsmentioning
confidence: 98%
“…They suggested rigorous prevention measure should be followed by the high-risk susceptible people. Mollalo et al (2020) mapped the spatial variability of the relationships between COVID-19 incidence rate and income inequality, median household, the proportion of black females and proportion of nurse practitioners using multiscale geographically weighted regression (MGWR).…”
mentioning
confidence: 99%
“…Economic, cultural, social, and human activities have been disrupted. Therefore, it is very important to study the prevalence of this disease, the rate of spread and predictability, to identify high-risk areas and affective factors (Mollalo et al, 2020).…”
mentioning
confidence: 99%
“…The GIS is an essential computer based tool for studying the spatial distribution, effective factors and spatio-temporal distribution of infectious diseases (Mollalo et al, 2020;Razavi Termeh and Sadeghi Niaraki., 2015). Despite the prevalence of COVID-19 in many countries around the world, there has been a notable increase in the number of cases and deaths in some countries such as the United States, Spain, and Italy (WHO, 2020a).…”
mentioning
confidence: 99%
See 1 more Smart Citation